The extent of the availability of the Quality Standards in Social Studies Textbook for Ninth Grade and History for Eleventh Grade in Kuwait: Perspectives of Teachers, Department Heads, and Supervisors (Damascus University Journal of educational and Psychologyical sciences, 2025)
The primary objective of this study was to assess the degree of the availability of the good textbook standards in Social Studies textbook for ninth grade and History for eleventh grade in Kuwait: perspectives of teachers, department heads, and supervisors. A convenient sample of 408 participants, including teachers, supervisors, and department heads, was recruited through a Google form link. Of these, 210 individuals assessed the History textbook, while 198 evaluated the Social Studies textbook. The questionnaire was distributed via email and social media. The questionnaire's validity was established through the face and factor analysis techniques, and reliability was assessed using Cronbach's Alpha and McDonald's Omega. The item-total correlation coefficient for all items was found to be significant at the 0.01 level. The results revealed that both textbooks achieved an "acceptable" level for the presentation of lessons and content subscales. In the case of the evaluation subscale, the 9th-grade textbook received an "acceptable" rating, while the 11th-grade textbook received a "good" rating. The format subscale achieved a "good" level for both textbooks. Similarly, the pictures, illustrations, and maps subscale were rated as "good" for both textbooks. The typing and printing of both textbooks received an "excellent" rating. Furthermore, the MANOVA analysis findings indicated no significant differences in the assessment of both textbooks based on gender, qualification, years of experience, or job type.
Keywords: Assessment; Evaluation; History Textbook, Social Studies Textbook; Textbook Standards; 9th Grade; 11th Grade